Estudo da transesterificação in situ daMicroalga scenedesmus sp. Visando à síntese de Ésteres para produção de biodiesel - Branco, Kemely Bruna Z. F (2013)
Research for alternative and/or complementary source for energy production are largely related to the production of biofuels, specifically biodiesel. The same is commonly recognized as a green alternative to petroleum diesel and come from renewable sources. Among the renewable sources for producing biofuels microalgae stand out, mainly, due to its high lipid content and its high productivity. Thus, the aim of this thesis was to study the synthesis of methyl and ethyl esters via in situ transesterification from the microalgae Scenedesmus sp. aiming at the production of biodiesel. Therefore, evaluated the influence of solvent, time, temperature and agitation parameters on yield esters. From the results, it was observed that the characterization of oil from microalgae is of extreme importance in determining the catalyst to be used in the reaction and to determine the fatty acid profile, a characteristic related to the final quality of biodiesel. It was also observed that the best results were obtained at 60 oC, regardless of alcohol used in the transesterification. Furthermore, verified that the agitation resulted in a small reduction in reaction time without leading to significant increases in yield esters. Among all the reactions carried out the combination of parameters that was more appropriate in this study was the use of ethanol, n-hexane at 60 oC, for 90 minutes, without agitation, with a value of 84.84 mg esters/ g dry weight. The results showed that ethanol is more efficient in producing esters, leading to higher yields at different reaction conditions. This result is extremely important, as well as lead to higher yields of esters using a reagent from renewable sources, and of course, its lower cost compared to methanol because of its availability in Brazil. The high yield values observed in ix esters indicated that the in situ transesterification presented with great potential use, and lead to cost reduction with reaction time and solvent use, when it is compared to the classic process of transesterification oil